6
$\begingroup$

Let $f$ given by

$$f(x) = g(x) + \int_0^x\left(g(x_1) + \int_0^{x_1} \left( g(x_2) + \int_0^{x_2} \ldots d_{x_n} \ldots \right) d_{x_2} \right) d_{x_1}$$

where $n \rightarrow \infty$ and $g(x)$ is strictly decreasing in $x$.

How can such an integral be solved or approximated for?

$\endgroup$
11
$\begingroup$

If $$h_n(x):=g(x) + \int_0^x\left(g(x_1) + \int_0^{x_1} \left( g(x_2) + \int_0^{x_2} \ldots d_{x_n} \ldots \right) d_{x_2} \right) d_{x_1} $$ converges to a limit function $h$, then the self similar nature of this expression implies that $$g(x)+\int_0^x h(t) \mathrm{d}t=h(x). $$ Differentiating gives $$g'(x)+h(x)=h'(x), $$ and using the integrating factor $e^{-x}$ gives $$e^{-x} g'(x)=(e^{-x} h(x))'. $$ Thus $$e^{-t} h(t) \big|_0^x=\int_0^x e^{-t} g'(t) \mathrm{d}t $$ or $$h(x)=e^x g(0)+e^x \int_0^xe^{-t} g'(t) \mathrm{d} t .$$ Finally, an integration by parts gives $$h(x)=g(x)+\int_0^x g(t) e^{x-t} \mathrm{d}t. $$

$\endgroup$
4
$\begingroup$

Observe:

$$ f(x) = g(x) + \int_0^{x} \left( g(x_1) + \int_0^{x_1} \left(... \right) \right) d_{x_1} = g(x) + \int_{0}^{x} g(x) + \int_{0}^{x}\int_0^{x_1} \left(... \right) d_{x_1}$$

Thus

$$ \frac{d}{dx} (f(x) - g(x)) = g(x) + \frac{d}{dx}\left( \int_{0}^{x}\int_0^{x_1} \left(... \right) d_{x_1} \right) = $$

By letting the inner: $\int_0^{x_1} \left(... \right) d_{x_1} = H(x_1)$ we are attempting to resolve

$$ \frac{d}{dx} (f(x) - g(x)) = g(x) + \frac{d}{dx}\left( \int_{0}^{x}H(x_1) d_{x_1} \right) = g(x) + H(x)$$

Thus we have that

$$ \frac{d}{dx} (f(x) - g(x)) = f(x) $$

Therefore

$$ f'(x) - g'(x) = f(x)$$

Now this can be solved relatively easily by noting

$$ f'(x) - f(x) = g'(x) $$

Thus

$$ e^x (f'(x) - f(x)) = e^x g'(x) $$

Thus

$$ (e^x f(x) ) ' = e^x g'(x) $$

Thus

$$ e^x f(x) = \int_{0}^{x} e^x g'(x) $$

Thus

$$ f(x) = e^{-x} \int_0^x e^{x} g'(x) dx $$

$\endgroup$
3
$\begingroup$

Yet another way: using the Cauchy formula for repeated integration, an $n$-fold integral can be replaced by one integral: $$ (J^k f)(x) = \int_0^{x}\dotsi \int_0^{t_{n-1}} f(t_1) \, dt_n \dotsm dt_1 = \frac{1}{(n-1)!} \int_0^x (x-t)^{n-1} f(t) \, dt, $$ which leads to the right-hand side becoming $$ g(x) + \sum_{k=1}^{\infty} (J^k g)(x) = g(x) + \int_0^x \sum_{k=1}^{\infty} \frac{(x-t)^{k-1}}{k!} g(t) \, dt = g(x) + \int_0^x e^{x-t} g(t) \, dt; $$ the interchange of the integral and sum using the convergence assumption and that $J$ is a contraction mapping on the space of functions.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.